The level of factionalism among elected barangay officials in the selected barangays of the municipality of Tanauan, Leyte. - Bagares, Jesabel Badem, et al; Blanco, Desiree Lynn C. (Jeabel Badem Bagares, 2010)
This is a descriptive-correlational study on the Level of Factionalism among elected barangay officials in the selected barangays of the Municipality of Tanauan, Leyte. The objectives of the study include: (1) to identify the significant socio-econoic and demographic (SED) profile of the elected barangay officials in the selected barangays of Tanauan, Leyte, (2) to determine the level of factionalism among elected barangay officials in the selected barangays of Tanauan, Leyte; (3) to find out the relationship between SED factors and the level of factionalism among elected officials in Tanauan Leyte and (4) to discover the implication of the level of factionalism among elected barangay officials on barangay governance.